New species of Lepidoptera for mainland Portugal (Insecta: Lepidoptera) - Nunes, J.; Silva, C.; Jesus, E. (SHILAP Revista de lepidopterología, 2021)
Six new species are added to the Lepidoptera fauna of mainland Portugal, resulting from the authors’ fieldwork in 2019 and 2020: namely Coleophora anitella Baldizzone, 1985, Aplota palpellus (Haworth, 1828), Anacampsis obscurella (Denis & Schiffermüller, 1775), Apomyelois bistriatella (Hulst, 1887), Eublemma amoena (Hübner, 1803) and Xestia sexstrigata (Haworth, 1809).